Multidrug-resistant novel Nocardia neocaledoniensis brain abscess in sarcoidosis. Issue 4 (19th April 2021) - Hazarika, Kasturi; Sahoo, Rasmi Ranjan; Ekbote, Digvijay; Dixit, Ajai Kumar; Marak, Rungmei S; Wakhlu, Anupam
Abstract : Central nervous system nocardiosis is a rare, life-threatening infection seen commonly in immunocompromised individuals. Nocardia neocaledoniensis is a novel species seldom causing infections in humans. We describe a patient of sarcoidosis on immunosuppression, who presented with altered sensorium due to a frontal lobe abscess secondary to N. neocaledoniensis infection. Despite appropriate and adequate antibiotic coverage, and timely surgical intervention, the patient succumbed to her illness on day 6 of hospitalisation. This case warrants the consideration of novel infections in patients on immunosuppression and the need for aggressive management.